Behind the search box : Google and the global internet industry - Yeo, ShinJoung (Geopolitics of information., 2023)
"Once seen as a harbinger of a new enlightened capitalism, Google has become a model of robber baron rapaciousness thanks to its ruthless monetizing of private data, obsession with monopoly, and pervasive systems of labor discrimination and exploitation. Using the company as a jumping-off point, ShinJoung Yeo explores the political economy of the search engine industry against the backdrop of the relationship between information and capitalism's developmental processes. Yeo's critical analysis draws on in-depth discussions of essential issues like how the search engine evolved into a ubiquitous commercial service, it's place in a global information business that is restructuring the information industry and our very social lives, who exactly designs and uses search technology, what kinds of workers labor behind the scenes, and the influence of geopolitics. An incisive look at a pervasive presence in our lives, Behind the Search Box places the search engine industry's rise and ongoing success within an original political economy of digital capitalism"--